Leadership and business model innovation in the internationalization of SMEs (Case Study in Pasuruan Furniture) - M. Fahrizal Hasibuan; Sudarmiatin Sudarmiatin; Imam Mukhlis (Cita konsultindo, 2023)
Based on the differences between small-scale and large-scale business model innovation, and between directing and empowering leadership, we examine how CEOs at UKM Furniture in Pasuruan led business model innovation during the internationalization process. Based on the case of a Furniture SME in Pasuruan, we develop a theoretical framework that points to two distinct patterns in the articulation between CEO leadership style and business model innovation. We demonstrate that small-scale business model innovation led by directive leadership results in more timely foreign market entries. However, to increase international sales, large-scale business model innovation is required. This is facilitated by the CEO's empowering leadership style.